Designing an emissions trading scheme for China with a dynamic computable general equilibrium model. (October 2016) - Tang, Ling; Shi, Jiarui; Bao, Qin
Abstract: To fulfill its Copenhagen pledges to control carbon emissions and mitigate climate change, China plans to establish a nationwide emissions trading scheme (ETS) in 2016. This paper develops a multi-sector dynamic computable general equilibrium model with an ETS module to study the appropriate ETS policy design, including a carbon cap, permit allocation and supplementary policies (e.g., penalty policies and subsidy policies). The main results are as follows. (1) To achieve China's Copenhagen pledge, the equilibrium nationwide carbon price is observed to be between 36 and 40 RMB yuan per metric ton. (2) The ETS policy has a cost-effective mitigation effect by improving China's production and energy structures with relatively little economic harm. (3) Various ETS sub-policies should be carefully designed to balance economic growth and carbon mitigation. In particular, the carbon cap should be set according to China's Copenhagen pledge. A relatively large distribution ratio of free permits, the output-based grandfathering rule for free permits, a penalty price (on illegitimate emissions) slightly above the carbon price, and a sufficient subsidy (from ETS revenue) are strongly recommended in the early stages to avoid significant economic loss. These designs can be adjusted in later stages to enhance the mitigation effect. Highlights: A dynamic CGE model is built for emissions trading scheme (ETS) in China. A new ETS module is formulated and introduced to capture diverse ETS designs. Designs for carbon cap, permit allocation and supplementary policy are considered. Different designs are simulated to give helpful insights into China's ETS policy.